The Agrarian Reform as a Path to Social Justice in Indonesia - Suci Rahmadani (Civic Governance and Public Administration, 2025)
This study aims to examine the obstacles to the implementation of agrarian reform that cause injustice for farmers. Inequality in land ownership, rooted in the colonial era, continues to cause multidimensional impacts, such as structural poverty, agrarian conflict, food dependency, and marginalization of indigenous communities. The research method used in this study is a qualitative method with a library research approach. The result show that agrarian inequality weakens agricultural development, deepens social disparities, and weakens state legitimacy. On the other hand, agrarian reform that is implemented comprehensively, including land redistribution, farmer empowerment, recognition of indigenous peoples rights, and integration with the sustainable development agenda can be a path to social justice as mandated by Pancasila and the Constitution.